Integrative metabolomics and transcriptomics profiling reveals differential expression of flavonoid synthesis in Ophiopogon japonicus (L. f.) Ker-Gawl. in adaptation to drought - Tingting Cheng; Juan Lin; Xia Zhou; Hongsu Wang; Xianjian Zhou; Xiaopeng Huang; TieZhu Chen (PLoS ONE, 2025)
Drought is one of the consequences of climate change that severely affects plant growth and development. Ophiopogon japonicus (L. f.) Ker-Gawl. (Chinese name: Chuanmaidong, abbreviated as CMD) is a commonly used herbaceous plant whose growth and development are strongly affected by drought. Here, we comprehensively analyzed the transcriptomic and metabolic responses of two CMD varieties (EP and CP) to drought stress. CP utilized a small number of differentially expressed genes to regulate a greater number of differential metabolites compared to EP, suggesting that it may be more drought tolerant. In addition, integrated transcriptome and metabolome analyses revealed that transcription factors such as WRKY, TIFY, and C2H2 regulate flavonoid synthesis in CMD. These findings provide ideas for in-depth analysis of the mechanism of CMD against drought stress, and provide a theoretical basis for breeding high-quality drought-tolerant varieties.